Understanding cancer predisposition in Singapore: what’s next - Jianbang Chiang; Tarryn Shaw; Joanne Ngeow (Singapore Medical Journal)
Knowledge of an underlying genetic predisposition to cancer allows the use of personalised prognostic, preventive and therapeutic strategies for the patient and carries clinical implications for family members. Despite great progress, we identified six challenging areas in the management of patients with hereditary cancer predisposition syndromes and suggest recommendations to aid in their resolution. These include the potential for finding unexpected germline variants through somatic tumour testing, optimal risk management of patients with hereditary conditions involving moderate-penetrance genes, role of polygenic risk score in an under-represented Asian population, management of variants of uncertain significance, clinical trials in patients with germline pathogenic variants and technology in genetic counselling. Addressing these barriers will aid the next step forward in precision medicine in Singapore. All stakeholders in healthcare should be empowered with genetic knowledge to fully leverage the potential of novel genomic insights and implement them to provide better care for our patients.